Analisa Pengaruh Digital Marketing, Informasi Produk, dan Impulse Buying terhadap Performa Marketing Melalui Keputusan Pembelian Beras: Studi di Pasar Tradisonal - Dhafin Fathur Rozi; David Sukardi Kodrat (Journal of Management and Social Sciences, 2026)
The increase in internet users in Indonesia presents a significant opportunity for business actors to market products through digital marketing, which allows transactions anytime and anywhere and influences purchasing decisions through complete and real-time product information. In addition, impulsive buying behavior, especially in areas like Ponorogo, which is rich in quality rice products with attractive discounts, also contributes to increased sales, impacting customer satisfaction, loyalty, and long-term customer value. Therefore, this study aims to examine the influence of digital marketing, product information, and impulse buying on purchasing decisions, as well as the ability of purchasing decisions to mediate the effect of digital marketing, product information, and impulse buying on marketing performance. This study uses a quantitative approach with a research sample of 104 respondents who are consumers of rice products in the Legi Ponorogo market. The data collection technique employed a questionnaire distributed online. The data analysis technique used is SEM PLS. The results of the study indicate that digital marketing and product information affect purchasing decisions, whereas impulse buying does not affect purchasing decisions. Furthermore, purchasing decisions have an impact on marketing performance. The results of the indirect effect show that purchasing decisions mediate the influence of digital marketing and product information on marketing performance, while purchasing decisions do not mediate the influence of impulse buying on purchasing decisions.